2020
DOI: 10.3390/ijerph17061906
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Subjective Oral Discomfort and Health-Related Quality of Life in the South Korean Elderly Population

Abstract: This study examined the relationship between oral discomfort and health-related quality of life (HRQOL) in the Korean elderly, using the datasets provided by the Korea National Health and Nutrition Examination Survey (KHNANES) over 6 consecutive years (2010–2015). A total of 13,618 participants aged 65 years and over were included in the final analysis. A complex sample logistic regression was performed to determine the impact of oral discomfort on HRQOL. The results revealed that toothache, masticatory discom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 26 publications
1
11
0
13
Order By: Relevance
“…The oral function, which encompasses a set of processes such as chewing, swallowing and phonation, is one of the points of quality of life. Thus, any type of injuries or harms to the oral cavity can impair and brings discomfort to the patient, as found in the results pointed out by the present study and confirmed by the study carried out in Quebec [21]. In addition to these problems, psychological and physical aspects may worsen the patient's condition.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The oral function, which encompasses a set of processes such as chewing, swallowing and phonation, is one of the points of quality of life. Thus, any type of injuries or harms to the oral cavity can impair and brings discomfort to the patient, as found in the results pointed out by the present study and confirmed by the study carried out in Quebec [21]. In addition to these problems, psychological and physical aspects may worsen the patient's condition.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the present research, which seeks to measure the impact of oral health status on the quality of life of adults, assumes that oral health is an "integral and inseparable part of an individual's general health", that is, it is notably a significant component of people's general health and quality of life [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…Saintrain et al 54 claimed that oral discomfort including teeth number or dry mouth can influence the level of well‐being of old people. Do and Moon 37 showed moreover that toothache, masticatory discomfort and pronunciation problems have an adverse impact on the health‐related quality of life of old people. Neither oral discomfort nor food ‐ related oral discomfort were presently found dependent on the age.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing sensations undergone while eating recently generated an increasing interest for industrials and researchers, especially related to the growing needs of senior populations. Nowadays, oral comfort experienced with foods can be explored through its unidimensional aspect by using visual, numerical or Likert scales 37 and/or its multidimensional aspects by using OHQoL questionnaires such as OHIP and GOHAI, 28 satisfaction questionnaires such as the McGill Satisfaction questionnaire 12 or the Dental Impact on Daily Living questionnaire, 38 and food comfortability 15 . The sensory dimension of the oral discomfort was presently assessed and measured in a similar way than pain, including quality, history, location and trigger factors of oral discomfort (with solid and liquid food products as reference).…”
Section: Discussionmentioning
confidence: 99%
“…The masticatory discomfort has a more severe negative effect on QOL in the dimensions of “self-care” and “normal activities.” As well as “pronunciation problems” had a similar effect on all aspects of the quality of the life. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%